(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
The historical type area of the Oxfordian Stage and its lowest subchronozone (Scarburgense Subchronozone of the Mariae Chronozone) are in Great Britain, in southern central (Oxford) and north eastern England (Scarborough), respectively. In neither district, however, are sequences sufficient complete to satisfy ICS requirements for a GSSP. Subsequent work in Haute Provence, south east France, however, has revealed considerably expanded sequences in Terre Noire facies which satisfy most ICS criteria and a GSSP for the Oxfordian Stage has now been formally proposed in this region. One British section, however, on the Dorset coast near Weymouth (Ham Cliff/ Redcliff Point), is relatively expanded and has the potential to complement the French candidate GSSP by yielding additional information on microfossil assemblages (e.g. ostrocods, foraminifera, coccoliths and holothurians). The sequence of ammonite faunas across the stage boundary at this and other key UK localities is reviewed, synthesised and correlated with the candidate GSSP in Haute Provence. This correlation can provide a framework within which additional information derived from UK sites, for instance from microfossil or geochemical studies, can be integrated to assist global correlation of the base of the Oxfordian Stage.